2015
DOI: 10.1111/str.12135
|View full text |Cite
|
Sign up to set email alerts
|

Digital Image Correlation Used for Experimental Investigations of Al/Mg Compounds

Abstract: Al/Mg compounds produced by hydrostatic extrusion exhibit unique characteristics in terms of high strength and low weight, which are required in lightweight safety parts. The compound interface between the core and sleeve is a brittle intermetallic phase consisting of Al 2 Mg 3 and Al 12 Mg 17 . However, a certain plastic deformability is required for subsequent processing of the semi-finished product by forming. To obtain a basic understanding of the deformation behaviour of the interface, the Digital Image C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…For the gauge length based computation, standard tensile test procedures were used as follows: where as , , and are the engineering stress, the engineering strain, the true stress, and the true strain, respectively [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 37 ]. In Equation ( 1 ), F , , , are the load applied, the initial area of sample cross-section, the length change and the gauge length, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the gauge length based computation, standard tensile test procedures were used as follows: where as , , and are the engineering stress, the engineering strain, the true stress, and the true strain, respectively [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 37 ]. In Equation ( 1 ), F , , , are the load applied, the initial area of sample cross-section, the length change and the gauge length, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the volume constancy, the longitudinal (length change) and transverse (width change) strains were computed from the tensile sample after roughly 20% plastic strain because the standard procedures generally suggest that the best range to determine the R –value is after the material yield point and before the tensile strength. The plastic strain ratio ( R ) can be determined as shown in Equation ( 3 ) [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1a,b shows a cross-sectional schematic view of the pressing billets with a Mg core and an Al cladding. The fracture and mechanical properties of the material composites have been investigated in detail by Lehmann [13,14] and Kirbach [15,16]. They found that the interface tensile strength at room temperature was 125 to 145 MPa, and the formability increased at elevated temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a good formability of the compound at high temperatures could be shown, which resulted partly in failure through large plastic deformation under bending. In these cases, the bending strength of the boundary layer is higher than the yield stress of the basic materials, which is important for further forging processes [21].…”
Section: Introductionmentioning
confidence: 99%